2014
DOI: 10.1063/1.4891323
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional percolation at the free water surface and its relation with the surface tension anomaly of water

Abstract: Structure of the nonionic surfactant triethoxy monooctylether C 8 E 3 adsorbed at the free water surface, as seen from surface tension measurements and Monte Carlo simulations J. Chem. Phys. 122, 124704 (2005) The percolation temperature of the lateral hydrogen bonding network of the molecules at the free water surface is determined by means of molecular dynamics computer simulation and identification of the truly interfacial molecules analysis for six different water models, including three, four, and five si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…42,47,61,62 Furthermore, using the ITIM method one of the so far unexplained anomalies of water, namely the surface tension anomaly has recently been successfully explained. 63,64 In this paper we present a detailed analysis of the liquid-vapor interface of acetonewater mixtures of different compositions, covering the entire composition range from neat water to neat acetone, using molecular dynamics computer simulation and ITIM surface analysis. In order to maintain the full miscibility of the two components, the simulations are performed using the PAC model of acetone and TIP5P-E model of water.…”
Section: Introductionmentioning
confidence: 99%
“…42,47,61,62 Furthermore, using the ITIM method one of the so far unexplained anomalies of water, namely the surface tension anomaly has recently been successfully explained. 63,64 In this paper we present a detailed analysis of the liquid-vapor interface of acetonewater mixtures of different compositions, covering the entire composition range from neat water to neat acetone, using molecular dynamics computer simulation and ITIM surface analysis. In order to maintain the full miscibility of the two components, the simulations are performed using the PAC model of acetone and TIP5P-E model of water.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of this intrinsic profile of various quantities can be of great help in understanding surface thermodynamics, as it provides the change of the corresponding quantity with the distance from the interface up to its convergence to the bulk phase value. For example, the intrinsic analysis has been essential to the investigation of surface properties of ionic liquids, [20][21][22][23] explanation of the surface tension anomaly of water, 24,25 immersion depth of surfactants in water, 26 oil-water interfaces, 27 structure of ionic aqueous solutions and their intrinsic interfacial potential, 28 the plausibility of the "HCN World" hypothesis, 29 as well as the adhesive properties of Newton black films. 30 Besides the exact location of the intrinsic surface itself, these methods provide in addition the full list of surface molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] The great physical relevance of the determination of the intrinsic liquid surface in computer simulation studies has recently been demonstrated by explaining the experimentally known but yet unexplained surface tension anomaly of water using intrinsic surface analysis. 25,26 A few years ago we have developed a method, called Identification of the Truly Interfacial Molecules (ITIM), which detects the intrinsic surface of a liquid phase by identifying the molecules that are right at its boundary with the opposite phase. 8 Comparing its performance with that of other intrinsic methods, ITIM turned out to be an excellent compromise between accuracy and computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…8 The ITIM method has successfully been applied to a number of liquid-liquid 9,13,27,28 and liquid-vapor 8,[10][11][12]25,26,[29][30][31][32][33][34][35][36][37][38] interfaces, including, among others, the liquid-vapor interface of neat methanol 10 and acetone, 38 and also to determine the intrinsic free energy profile of ionic and non-ionic penetrants across such interfaces. 39,40 In this paper, we present a detailed investigation of the liquid-vapor interface of acetone-methanol mixtures in the entire composition range from neat acetone to neat methanol on the basis of molecular dynamics computer simulations and ITIM analysis, using a potential model combination that is able to excellently reproduce the mixing properties of the two components.…”
Section: Introductionmentioning
confidence: 99%